Co-correspondence analysis of fish and macroinvertebrate assemblages in relation to environmental variables in the Bheri and Babai river systems, Nepal - Khatri, Kumar; Shrestha, Santoshi; Jha, Bibhuti Ranjan; Khadka, Uddhab Raj; Gurung, Smriti (Nepalese Journal of Zoology, 2025)
This study investigates the co-occurrence patterns of fish and macroinvertebrate assemblages in the Bheri and Babai rivers of Western Nepal and their relationships with environmental variables. Sampling was conducted at 10 sites encompassing four seasons in 2018 using electrofishing and standardized macroinvertebrate collection protocols. The physico-chemical parameters and substrate composition were recorded at each site. The seasonal abundance data from all sites for both fish and macroinvertebrates were pooled and used in the symmetric Co-correspondence Analysis (CoCA). The CoCA revealed a very strong shared community structure between fish and macroinvertebrates, accounting for more than 99% of the total shared variance in both rivers (Bheri: 99.6%; Babai: 99.7–99.8%). Within this shared structure, the first two CoCA axes captured approximately 57% of the shared variation, reflecting clear ecological gradients in each system. The Envfit analysis identified sulphate, electric conductivity (EC), and temperature as significant drivers in the Bheri River system, while EC and substrate heterogeneity particularly boulder and gravel, were most influential in the Babai River system. These findings suggest that the Bheri River system assemblages are primarily structured by water chemistry, whereas the Babai River system is shaped by physical habitat complexity. The strong biotic congruence between fish and macroinvertebrates highlights their potential as complementary bioindicators, offering an integrated framework for biodiversity assessment and management in Nepalese river ecosystems.